Compacton matter waves in binary bose gases under strong nonlinear management - Abdullaev, Fatkhulla; Abdul Hadi, Muhammad Salihi; Salerno, Mario; Umarov, Bakhram (American Physical Society, 2014)
The existence of compacton matter waves in binary mixtures of quasi-one-dimensional Bose-Einstein condensates in deep optical lattices, and in the presence of nonlinearity management, is demonstrated. For this, we derive an averaged vector discrete nonlinear Schr¨odinger equation (DNLSE) and show that compacton solutions of different types can exist as stable excitations. Stability properties are studied by linear analysis and by direct numerical integrations of the DNLSE system and their dependence on the inter- and intraspecies scattering lengths investigated. We show that under proper management conditions, compactons can be very robust excitations that can emerge spontaneously from generic initial conditions. A possible experimental setting for compacton observation is also discussed.